Case study of academic achievement in technological subjects: the gender orientation - Cadavieco, Javier Fombona (2019)
Traditionally science and technology have been linked to male students. Currently, this division no longer exists in many places. Research related to the gender topic still has special interest because of its social significance. This paper analyzes the differences in academic achievement in certain subjects and on the educational level of secondary schooling. Specifically we analyze a case in Spain involving a sample of students. The result reveals that girls exceed boys in mastering the academic disciplines. Although nowadays there are no subjects specific to men or women, significant differences are detected when these students deal with higher engineering studies. The scientific contextualization has highlighted the early motivation among the students, and our specific findings show the reduced decision to pursue higher technical studies, which do not correlate positively with the academic achievement obtained at pre-university levels. Moreover, the educational action in secondary schooling reduces the difference in the academic results of certain subjects. Despite this egalitarian tide, current trends turn to a limited growth of students in these training specialties, and if one starts with an initial small number of women, it is unlikely that they will become a dominant element in engineering.